Uncovering substructure with wavelets: proof of concept using Abell 2744 - Schwinn, Johannes; Bartelmann, Matthias (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. A recent comparison of the massive galaxy cluster Abell 2744 with the Millennium XXL (MXXL) N-body simulation has hinted at a tension between the obs